2010
DOI: 10.4172/1948-5956.1000050
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Interferon γ Decreases Levels and Activity of Key Cell Cycle Proteins Resulting in Severe Growth Arrest of the Human Non-Transformed Cell Line, WISH

Abstract: Interferon g (IFNg), a potent inhibitor of proliferation, inducer of apoptosis, and an immune modulator of mammalian cells, has been used as an anticancer agent in cancer therapy. Several molecular mechanisms, depending upon the differences in the lineage of transformed cell targets, have been elucidated for the growth inhibition or apoptosis of target cancer cells by IFNg. However, its mechanism of action on normal cells needs to be understood from the point of view of: (i) The effect of IFNg on non-transform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Enhanced delivery of encapsulated DNA by membrane fusion, protection of nucleic acids from nuclease activity, targeting to specific cells, delivery into a variety of cell types besides protoplasts by entry through plasmodesmata [50] .In Liposome based gene therapy there is no toxicity potential in humans and plants [51].Our results should stimulate efforts to develop plant-based technologies for the removal of pollutants from contaminated environments [52]. Specific molecular changes have been suggested to be the reasons for the growth of gene therapies [53] a liposomal delivery system requires a complete understanding of the physicochemical characteristics of the drugliposome system [54].…”
Section: Liposome Gene Transfermentioning
confidence: 94%
“…Enhanced delivery of encapsulated DNA by membrane fusion, protection of nucleic acids from nuclease activity, targeting to specific cells, delivery into a variety of cell types besides protoplasts by entry through plasmodesmata [50] .In Liposome based gene therapy there is no toxicity potential in humans and plants [51].Our results should stimulate efforts to develop plant-based technologies for the removal of pollutants from contaminated environments [52]. Specific molecular changes have been suggested to be the reasons for the growth of gene therapies [53] a liposomal delivery system requires a complete understanding of the physicochemical characteristics of the drugliposome system [54].…”
Section: Liposome Gene Transfermentioning
confidence: 94%
“…Results indicated that ATRA plus IFN-γ activated multiple molecular mechanisms for increasing apoptosis in human glioblastoma in vivo [12]. Interferon γ (IFNγ), a potent inhibitor of proliferation is an inducer of apoptosis [13]. Tissue microarrays (TMAs) have been commonly utilized in translational research to rapidly screen numerous biomarkers in large samples [14].…”
Section: Increasing Apoptosis In Human Glioblastoma T98g Xenograftmentioning
confidence: 99%
“…These can be made in the laboratory and used to shrink or stop the growth of cancer cells. Some interferon's stimulate the growth of lymphocytes which then destroys the cancer cells [66,67]. The side effects with this include fever, chills, muscle and joint aches, and fatigue.…”
Section: Interferonmentioning
confidence: 99%